Legal aspects on right to access to land of investors through land use rights transactions in Vietnam - Thai, Luu Quoc (Technium Social Sciences Journal, 2021)
Access to land and the stability in land use” is one of 10 indicators to measure the competitiveness of the localities in attracting investment in Vietnam. Until the present time, the access to land through land use rights transactions of investors is still discriminated, especially for foreign-invested enterprises. Therefore, this article will discuss the “opportunities” to access to land (or land use rights) of investors, through the land use right transactions (in the secondary market) in the Vietnamese current Land law to point out the limitations of the Vietnamese land laws